Parkinson’s disease – a frequent cause of dementia - Wardęszkiewicz, Marta; Markowiak, Szymon; Jabłońska, Wiktoria; Kasprzak, Amelia; Świercz, Maciej; Truchta, Monika; Mańkowska, Aleksandra; Kolano, Agata; Pejas, Anna (Journal of Education, Health and Sport, 2024)
Introduction and Purpose. Parkinson’s disease (PD) is a progressive neurodegenerative disorder with characteristic motor symptoms and often overlooked non-motor manifestations, including dementia. This research article aims to enhance our understanding of PD and its complex clinical course, ultimately contributing to improved patient care and management. Moreover, it is important to raise awareness of cognitive impairment associated with Parkinson’s disease, as it is an aspect of social exclusion and disability Material and method. This study is based on medical articles collected from the PubMed database spanning the years 2015-2023. The research was conducted through the analysis of keywords such as Parkinson’s disease, dementia, diagnose, tremor, cognitive impairment. Brief description of the state of knowledge. Parkinson’s disease is established as a movement disorder, primarily attributed to the loss of dopaminergic neurons in the substantia nigra. Although there is no cure for PD, treatment options have expanded, including pharmacological and non-pharmacological approaches. Early diagnosis is vital for effective management, and a multidisciplinary approach is crucial in addressing the diverse needs of PD patients. Summary. Parkinson’s disease, a multifaceted neurodegenerative disorder, presents a complex clinical picture that extends beyond motor symptoms to include dementia. This review highlights the etiology, clinical manifestations, diagnostic criteria, differential diagnosis, various treatment modalities. Understanding of Parkinson’s disease, particularly its association with dementia, is essential for healthcare professionals and researchers to provide comprehensive care.